Produção e Distribuição de Matéria Seca e Composição Bromatológica de Cultivares de Alfafa (Medicago sativa L.) - Monteiro, ALG; Costa, Ciniro [UNESP]; Silveira, Antonio Carlos [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
The objective of this research was to evaluate dry matter production (DMP), seasonal distribution (SD) and chemical composition of crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) of seventeen alfalfa cultivates: Creole, Florida 77, P555, P581, Moapa, Gilboa, 34 Linea, C/W 8754, C/W 4468, C/W 86, C/W 8746, Hunter Field, Trifecta, Sequel, CUF 101, Aurora e Siriver. A complete randomized blocks experimental design, with three replicates in a split plot on time scheme, was used. For DMP and SD, the cultivates were in the main plot and cuts in the subplots. For chemical composition, cultivates were also the main plots, and seasons of the year, summer and winter, the subplots. There were no differences among cultivates for the annual average dry matter production (12,08 t/[ha.year]) and SD (35% in the winter). There were differences in the chemical composition, among cultivates for CP and significant interaction among cultivates and the seasons of year for NDF and ADF. All cultivates showed similar potential production and seasonal distribution of dry matter. The alfalfa quality in the winter was better than in the summer.
Dry matter production and seasonal distribution and chemical composition of alfalfa cultivates (Medicago sativa L.)
Keywords: chemical composition; alfalfa cultivates; seasonal distribution alfalfa yield